2020
DOI: 10.1016/j.jctube.2020.100193
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding the gaps in DR-TB care cascade in Nigeria: A sequential mixed-method study

Abstract: Background Despite the availability of free drug-resistant tuberculosis (DR-TB) care in Nigeria since 2011, the country continues to tackle low case notification and treatment rates. In 2018, 11% of an estimated 21,000 cases were diagnosed and 9% placed on treatment. These low rates are nevertheless a marked improvement from 2015 when only 3.4% were diagnosed and 2.3% placed on treatment of an estimated 29,000 cases. This study describes the Nigerian DR-TB care cascade from 2013 to 2017 and consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 47 publications
(52 reference statements)
2
13
0
1
Order By: Relevance
“…Many people also believe that government health services are not of good quality [ 54 , 55 ]. Addressing people’s knowledge gaps through community awareness programmes [ 23 , 56 ] and adopting intensive, state-of-the-art, and multidimensional interventions to support active case finding can dramatically improve local TB epidemics [ 3 , 29 ]. In one such programme, an awareness campaign and cell phone-based provisional cash transfers to all people screened at private clinics doubled TB notifications [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many people also believe that government health services are not of good quality [ 54 , 55 ]. Addressing people’s knowledge gaps through community awareness programmes [ 23 , 56 ] and adopting intensive, state-of-the-art, and multidimensional interventions to support active case finding can dramatically improve local TB epidemics [ 3 , 29 ]. In one such programme, an awareness campaign and cell phone-based provisional cash transfers to all people screened at private clinics doubled TB notifications [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another reason for not seeking care with health facilities is that patients may not have care-seeking behaviour [ 56 ]. Public education strategies via TV, radio, or other electronic social media can modify this behaviour.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our conceptual framework (figure 1) is derived from existing literature29 31–33 and highlights two main types of delays along pathways to TB care: health-seeking and health system delays. Health-seeking delays are defined as the time it takes from symptom onset to patients recognising their symptoms and seeking care from a healthcare provider.…”
Section: Methodsmentioning
confidence: 99%
“…These delays can lead to three major gaps or missed opportunities in accessing TB care: Gap 1 includes those who never access TB testing, Gap 2 are those who access testing but are not diagnosed and Gap 3 includes those diagnosed but not treated. These gaps result in prolonged illness, disease transmission, increased risk of drug-resistant TB and death 1 32 33. Studies done in Nigeria before the pandemic identified Gap 1 as the biggest challenge in TB control, followed by Gap 2 5 32 35 41…”
Section: Methodsmentioning
confidence: 99%